A Study of Bilingual Education and Communicative Competence at Junior Secondary School - Refi Ranto Rozak (Jurnal Penelitian Pendidikan, 2014)
The concern of the paper is the bilingual education conducted at SMP Negeri I Bojonegoro.The study attempts to investigate and to find out the research problems dealing with theinfluence of bilingual education on students’ speaking English competence, communicativeenvironment motivating students to have awareness to speak in English, bilingualmethodology in the classrooms, and the impediments encountered by the teachers andstudents in employing bilingual learning. The research design of the study is descriptivequalitative using triangulation technique in collecting the required data. The population isseventh and eighth graders students of SMPN 1 Bojonegoro in the academic year of2013/2014. Meanwhile, the theoretical samples of the study are taken based on the use ofbilingual across subject contents (sciences and mathematics) at year VII A and VIII A. Theresult of the study shows that the program raises the students’ and teachers’ awareness inbilingual education as it is used in specific contents subject. It consequently enhances themotivation for foreign language learning.